Does Causality Technique Matter to Savings-Growth Nexus in Malaysia? (Malaysian Management Journal, 2009)
The intention of this study was to investigate whether the causal inference between savings and economic growth in Malaysia is sensitive to the particular causality tests employed to ascertain the causal relationship. This study covered quarterly data from 1991:Q1 to 2006:Q3. The results suggested that the causal relationship between savings and economic growth in Malaysia is not sensitive to the particular causality test used. Thus, causality test plays no role in explaining the inconsistency causality result of savings and economic growth. Ultimately, causality test does not matter to savings-growth nexus for Malaysia.